Feasibility of a novel MEG-compatible proprioceptive stimulator of the knee joint - Byman-Vornanen, Anni (2024)
Introduction: Proprioceptive afference refers to the transmission of information about body’s position and movements from proprioceptors to the brain. This information is crucial for sensorimotor control, with muscle stretch reflexes, such as the patellar tendon reflex, playing essential roles. Magnetoencephalography (MEG) provides a non-invasive means to examine cortical processing of the proprioceptive afference to peripheral stimuli. While evoked cortical responses have been investigated for most sensory domains, a gap exists in lower-limb proprioception research, particularly at the knee joint. In addition, the MEG environment requires special attention from the stimulation devices used, since stimulators must be designed to avoid generating interference with magnetic signals. Therefore, the objective for this study was to test the feasibility of a MEG-compatible proprioceptive stimulator (reflex hammer) of the knee joint and to provide preliminary insights into the cortical processing of proprioceptive afference of the patellar tendon reflex.